Novel Donor-Acceptor Polymers for Solar Cells - Bodapati, Jagadeesh Babu (Eastern Mediterranean University (EMU), 2011)
ABSTRACT: The process of photo conversion in most opto-electronic devices includes transfer of absorbed solar energy to convert it into either chemical or electrical energy. Perylene and naphthalene dyes are characteristic n-type conjugated organic materials and are very attractive with great potential applications in the photonic field as they possess high stabilities, absorption capacities, and light emitting properties. The focus of this work is the synthesis, structure, photophysical, and electrochemical properties of oligomer dyes based on perylene and naphthalene chromophores, named, perylene-3,4,9,10-tetracarboxylic acid-Bis-(N,N_-Bis 2-[2-(2-{2-[2-(2- hydroxy-ethoxy)-ethoxy]-ethoxy}-ethoxy)-ethoxy]-ethylpolyimide (EOPPI), naphthalene-1,4,5,8-tetracarboxylic acid-Bis-(N,N_-Bis 2-[2-(2-{2-[2-(2-hydroxyethoxy)- ethoxy]-ethoxy}-ethoxy)-ethoxy]-ethylpolyimide (EONPI). Additionally, two previously synthesized n-type materials based on the same chromophores were considered to explore the electrochemical properties concerning photovoltaic devices. The compounds are characterized in detail by studying their optical, photophysical, thermal and electrochemical properties using the techniques IR, GPC, UV-vis, Fluorescence, DSC, TGA and Cyclic, squarewave voltammetries. Both oligomeric dyes exhibited attractive color tunability with different lightemitting properties. They possessed outstanding solubilities, molar absorption coefficients, thermal stabilities and electrochemical stabilities and reversibilities. The strong solvent dependent photophysical and electrochemical properties of EONPI, including the large shift of excimer emission maximum, makes the oligomer potential candidate for various photo sensing applications. Keywords: Perylene, naphthalene, solar cell, photovoltaic, color tunability. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Birçok opto elektronik aygıtlarda foton dönüsümü süreci, absorblanan solar enerjinin kimyasal veya elektriksel enerjiye dönüsümünü içermektedir. N tipi yarıiletken özellikler sergileyen perilen ve naftalen boyaları yüksek kararlılık, absorblama yetenegi ve ısın yayma özellikleri nedeniyle, fotonik alanda çok ilgi uyandıran konjüge organik materyallerdir. Tez kapsamında, perilen ve naftalen kromoforları esaslı iki oligomer, perilen- 3,4,9,10-tetrakarboksilik asid-bis-(N,N_-bis 2-[2-(2-{2-[2-(2-hidroksi-etoksi)-etoksi]- etoksi}-etoksi)-etoksi]-etilpoliimid (EOPPI) ve naftalen-1,4,5,8-tetrakarboksilik asidbis-( N,N_-bis 2-[2-(2-{2-[2-(2-hidroksi-etoksi)-etoksi]-etoksi}-etoksi)-etoksi]- etilpoliimidin (EONPI) sentezine, yapılarına, fotofiziksel ve elektrokimyasal özelliklerine odaklanılmıstır. Ayrıca, Daha önce sentezlenmis olan benzer kromoforlar esaslı iki ayrı n-tipi materyalin elektokimyasal özellikleri fotovoltaik aygıtlarla ilgili olarak arastırılmıstır. Sentezlenen maddelerin optik, fotofiziksel, termal ve elektrokimyasal özellikleri IR, GPC, Uv-vis, emisyon, DSC, TGA ve CV ölçümleri ile detaylı arastırılarak tanımlanmıstır. Her iki oligomerik boya da degisik ısık yayma özelliginde olup ilgi çekici renk ayarlanılabilirlilik özelligi sergilemistir. Olaganüstü çözünürlük, molar absorblama sabitleri, termal kararlılık ve tersinir elektrokimyasal kararlılık özelliklerine sahiptirler. Kuvvetle çözgene baglı fotofiziksel ve elektrokimyasal özellikler ve maksimum ekzimer emisyonunda büyük kayma sergileyen EONPI oligomeri degisik foto duyarlı uygulamalar için potansiyel bir adaydır. Anahtar kelimeler: Perilen, naftalen, solar hücre, fotovoltaik, renk ayarlanabilirlilik.
Doctor of Philosophy in Chemistry. Thesis (Ph.D)--Eastern Mediterranean University, Faculty of Arts and Science, Dept. of Chemistry, 2011. Supervisor: Prof. Dr. Huriye İcil.
Keywords: Chemistry; Perylene - Naphthalene - Solar Cell - Photovoltaic - Color Tunability